Whole-genome sequence-based comparison and profiling of virulence-associated genes of Bacillus cereus group isolates from diverse sources in Japan - Okutani, Akiko; Inoue, Satoshi; Noguchi, Akira; Kaku, Yoshihiro; Morikawa, Shigeru (BMC microbiology, 2019)
The complete genome sequences of 44 Bacillus cereus group isolates collected from diverse sources in Japan were analyzed to determine their genetic backgrounds and diversity levels in Japan. Multilocus sequence typing (MLST) and core-genome single-nucleotide polymorphism (SNP) typing data from whole-genome sequences were analyzed to determine genetic diversity levels. Virulence-associated gene profiles were also used to evaluate the genetic backgrounds and relationships among the isolates. The 44 B. cereus group isolates, including soil- and animal-derived isolates and isolates recovered from hospitalized patients and food poisoning cases, were genotyped by MLST and core-genome SNP typing. Genetic variation among the isolates was identified by the MLST and core-genome SNP phylogeny comparison against reference strains from countries outside of Japan. Exploratory principal component analysis and nonmetric multidimensional scaling (NMDS) analyses were used to assess the genetic similarities among the isolates using gene presence and absence information and isolate origins as the metadata. A significant correlation was seen between the principal components and the presence of genes encoding hemolysin BL and emetic genetic determinants in B. cereus, and the capsule proteins in B. anthracis. NMDS showed that the cluster of soil isolates overlapped with the cluster comprising animal-derived and clinical isolates. Molecular and epidemiological analyses of B. cereus group isolates in Japan suggest that the soil- and animal-derived bacteria from our study are not a significant risk to human health. However, because several of the clinical isolates share close genetic relationships with the environmental isolates, both molecular and epidemiological surveillance studies could be used effectively to estimate virulence in these important pathogens.